Implementasi Profile matching Pada Pemilihan Calon Jemaah Haji - Muhammad Fauzi; Y Yudi; Frinto Tambunan; Frans Ikorasaki (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Indonesia is one of the countries with the largest number of pilgrims in the world. The problem that often occurs when departing for Hajj, is because of the large amount of time used for the selection of pilgrims who will depart. One solution that can be used to solve these problems is to implement a decision support system. The criteria used in this study were health, age, year of registration, queues, history of illness and occupation. Researchers use the profile matching method to be applied in the decision support system for selecting pilgrims because researchers consider this method to be able to provide good decision results. The result of this study is to apply the profile matching method in the decision support system for the selection of pilgrims so that decision makers can be assisted in making decisions for pilgrims who will depart for the pilgrimage